Improving shore power project economics at the Port of Aberdeen. (June 2023) - Bullock, Simon; Higgins, Eliott; Crossan, James; Larkin, Alice
Abstract: Shore power is one of just a few technologies available to the shipping sector that has potential to deliver carbon reductions this decade in line with the Paris Climate Agreement. Shore power connects ships to land-side electricity grids, reducing fossil fuel use while at berth in port and at the same time improving air quality. It is also an enabling technology for the future deployment of electric vessels, allowing battery recharge. Despite being a proven technology, global deployment has been slow, with the literature pointing to clear economic barriers to its uptake. These include high capital costs for ports, high taxes on land-side electricity and the global lack of taxation on ships' fuel oils. Yet there is a gap in understanding around how to overcome these barriers. Here, a case-study of the Port of Aberdeen in Scotland is used to explore how the economic case for a shore-power system can be improved. A multi-criteria analysis and techno-economic assessment, coupled with port-user and supplier engagement, applicable to other port contexts, sheds light on how to create the much-needed acceleration of shore-power deployment. By building a collaborative approach between the port, ship operators and national government, project viability can be unlocked to more closely align the sector's future carbon pathway with the high ambitions laid out in Paris 2015. Highlights: Shore power cuts greenhouse gas emissions and improves air quality. Shore power is deployable now but has economic barriers. Government support on tax and capital funding can accelerate shore power deployment. Co-operation between ports, ship operators and Government can deliver viable projects.